Language, politics and identity in the novels of Ahmadou Kourouma (2012)
Facts are vital parameters not only in the sciences, history and translation studies but also in literature Facts are the back-hone of human discussions irrespective of the nature of things discussed. To avoid attacks for political reasons, some Francophone Postcolonial African writers, create imaginary spaces in their novels and embellish them with facts. This is for instance, the preoccupation of Ahmadou Kourouma in his debut novel, Les soleils des independances (1970), and others. The objective of this paper is to show Kourouma’s commitment as a literary linguist, politician, historian, geographer, and indeed as an iconoclastic writer. The issue of identity is also addressed in the analysis of Kourouma’s works. This study, therefore, adopts a narrative analysis of data collected from Ahmadou Kourouma’s Les soleils des independances (1970), Monne, outrages et defis (1990), En attendant le vote des betes sauvages (1998) Allah n ’est pas oblige (2000), and Quand on refuse on dit non (2004). Special attention is paid to critica works of linguists, political theorists, translators and literary scholars among others, to buttress our discourse. Kourouma is known for his language revolution, political discourse, translation skills and his quest for identity. In fact, Kourouma’s coloration of French language with Malinke, his mother-tongue stands like pillars to solidify his creative work and to promote African languages and identity. Needless to say that facts and spaces are parameters responsible for the gradual development of Kourouma’s novels for they allow his protagonists to complete their journey in the process of actualizing their destiny.